Application of the Teams Games Tournament Learning Model Based on the Number Monopoly Game in Improving Elementary School Students' Mathematical Understanding - Lamusu, Chen Aldia; Kadir, Kadir; Kahar, Aris Armeth Daud Al; Asma, Andi; Zainal, Nur Fitriani; Santoso, Agung Budi (Journal of Elementary Educational Research, 2024)
This research aims to improve mathematics learning outcomes on statistics and data in class V at Inpres Durian Elementary School by implementing the Teams Games Tournament learning model assisted by the number monopoly game. This research uses the classroom action research method, with four stages: planning, implementation, observation and reflection. This research consists of two cycles, each consisting of 8 meetings for teaching and learning activities and one meeting for learning outcomes tests. The subjects of this research were 18 class V students at Inpres Durian Elementary School. The data collection techniques used are tests of student learning outcomes, observation of student and teacher activities and documentation. The results of this research show that the application of the Teams Games Tournament learning model assisted by the number monopoly game on the subject of statistics and data can improve the learning outcomes of class V students at SD Inpres Durian from a pre-cycle average score of 48.33 to 72.22 in cycle I and 85.55 in cycle II. In addition, classical learning completeness in the pre-cycle was 15.78%, increasing to 66.67% in cycle I and 88.88% in cycle II. The results of observing teacher activities in cycle I were very good and continued to persist in cycle II. Meanwhile, the results of observations of student activities increased from the adequate category in cycle I to very good in cycle II. Referring to the research success indicators, which set a KKM of 70 and a classical completion score of 85% in the good category, it can be concluded that implementing the Teams Games Tournament learning model assisted by the number monopoly game in class V at Inpres Durian Elementary School can improve learning outcomes in the mathematics subject.